Vander Woude's syndrome: The rarest of the rare - Shweta Advani; Suma Sogi; Shivayogi Hugar; Kiran Bhatt (Wolters Kluwer Medknow Publications, 2012)
One of the most common developmental defects seen in south India is cleft lip and palate. Among them a few are associated with lip pits and termed as Vander Woude's syndrome. The early diagnosis of this rare syndrome is very necessary followed by a multidisciplinary approach. It is also necessary to differentiate this syndrome from the other syndromes which may present similar features. A case report of the same is presented here requiring a multidisciplinary approach for a functional and esthetically pleasing outcome.